Bruns Syndrome Caused by Intraventricular Neurocysticercosis: Literature Review - Silva, Guilherme Gago da; Ferreira, Nelson Pires; Britz, João Pedro Einsfeld (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Bruns syndrome is one of the clinical presentations of intraventricular neurocysticercosis, and it is characterized by episodes of headache, vertigo and vomiting. The intraventricular form of neurocysticercosis occurs in 7% to 20% of the cases, and it is more serious than the intraparenchymal form. The management is primarily surgical, associated with pharmacological therapy with anthelmintic drugs and corticosteroids. We report the case of a patient who presented Bruns syndrome due to neurocysticercosis.
Keywords: neurocysticercosis; cysticercus; neurosurgery